Energy resilience in disaster-prone regions: the role of portable and modular solar power systems - Sutikno, Tole; Facta, Mochammad; Aji, Wahyu Sapto; Handayani, Lina; Arsadiando, Watra; Purnama, Hendril Satrian (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
Energy resilience is a critical requirement in disaster-prone regions, where electrical infrastructure is highly vulnerable to natural hazards and prolonged power outages. Portable and modular solar power systems have emerged as promising solutions for enhancing resilience by enabling decentralized, rapidly deployable, and grid-independent energy supply. This paper presents a comprehensive review of the role of portable and modular photovoltaic-based power systems in improving energy resilience from a power electronics perspective. The review synthesizes recent literature on resilience concepts, system architectures, and converter-based control strategies relevant to emergency energy applications. Particular emphasis is placed on DC-first and hybrid AC/DC architectures, modular converter topologies, battery management systems, and energy management strategies that support reliable and fault-tolerant operation under variable and uncertain conditions. Practical deployment and performance considerations, including scalability, robustness, monitoring, and usability in disaster environments, are also discussed. The findings indicate that well-designed portable and modular solar power systems can significantly reduce recovery time, improve operational continuity, and decrease reliance on centralized grids and fuel-based generators. This review identifies key technical challenges and research opportunities to guide future development of resilient power electronic-based energy systems for disaster response and recovery.